2021
DOI: 10.13189/saj.2021.090406
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Small Side Games (SSG) in Forearm Pass Volleyball Use Application in Mobile Phone

Abstract: The learning model used is based on the material provided and adapted to the situation and conditions in the field. There needs to be a game modification so that students can actively participate in learning volleyball games. The purpose of this study was to see the effectiveness of the small side games learning model on the mobile phone application to increase student participation in physical education. The research method used was an experiment with a control group. Participants involved in the study were 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Tested the effectiveness of the passing learning model based on small side games using an application on mobile phones that had been developed for junior high school students. The results showed that there was an increase in the skills of the volleyball game arm passing using the small side game learning model, namely t0 7,884 and t table 1,292. db 82 and = 0.05 besides that there was an increase in student participation [18].…”
Section: Discussionmentioning
confidence: 86%
“…Tested the effectiveness of the passing learning model based on small side games using an application on mobile phones that had been developed for junior high school students. The results showed that there was an increase in the skills of the volleyball game arm passing using the small side game learning model, namely t0 7,884 and t table 1,292. db 82 and = 0.05 besides that there was an increase in student participation [18].…”
Section: Discussionmentioning
confidence: 86%
“…Pembelajaran pola gerak dasar harus disusun sedemikian rupa sehingga apapun jenis permainan yang kita berikan kepada siswa, selanjutnya harus diarahkan kepada gerakan yang efisien dan pembelajaran efektif. Lewat permainan sederhana ini dapat meningkatkan partisipasi siswa dalam proses pembelajaran pendidikan jasmani (Ningrum et al, 2021). Pembelajaran dengan pendekatan permainan bisa dilakukan tanpa menggunakan alat, atau bahkan bisa menggunakan alat bantu apa saja, sehingga diharapkan terciptanya produk yang merepresentasikan kebutuhan mitra pengabdian ini.…”
unclassified